Study to Determine the Antimicrobial Sensitivity and Resistance pattern of Various Strains against Commonly prescribed Antibiotics (Medical Forum Monthly, 2024)
Objective: The main objective of this study was to determine the sensitivity and resistance of various bacterial strains both gram negative and gram positive against commonly used antibiotics.Study Design: Experimental / Retrospective study.Place and Duration of Study: This study was conducted in Hayatabad Medical Complex at Microbiology Laboratory for a period of six month studies from 6.8.2013 to 10.02.2014.Materials and Methods: The study was conducted in which both in-door and out-door patients were randomly selected for this specified period of time. Bacterial strains used were Staphylococcus Aureus, Escherichia Coli, Pseudomonas Aeruginosa and Proteus Mirabilis against commonly prescribed antibiotics i.e; Ceftraixone, Amoxicillin, Amikacin and Cefepime and to find out the sensitivity and resistance pattern.Results: Among the selected antibiotics Ceftraixone was found to be sensitive in 84.6% of out-door patients and 75 % of in-patient against Pseudomonas Aeruginosa, 71.4% of out-door patients and 68.4% of in-patients against Escherichia Coli, 52% of out-door patients and 60% in-patient against Staphylococcus Aureus and least sensitive against Proteus Mirabilis 25% out-patients and 16.7% in-patients. Amoxicillin was 40%, 6.6% and 0% sensitive in in-patients and 16%, 17.1%, 0.7% and 0% in out-patients against Staphylococcus Aureus, Escherichia Coli, Pseudomonas Aeruginosa and Proteus Mirabilis respectively. Amikacin was 44%, 35%, 33.3% and 0% sensitive in in-patients and 36%, 37.2%, 32% and 0% in out-patients against Staphylococcus Aureus, Escherichia Coli, Pseudomonas Aeruginosa and Proteus Mirabilis respectively. Cefepime was most sensitive against Proteus Mirabilis 25% in out-door patients and 16.7% in in-door patients while least sensitive against Pseudomonas Aeruginosa both in out-door and in-door patients.Conclusion: It is concluded from the results obtained that Ceftraixone, Amoxicillin and Amikacin were more than 60% sensitive against the selected strains of bacteria except Proteus Mirabilis while Cefepime is least sensitive i.e; less than 25% against all these antibacterial strains. These results should be considered in future prescribing of antibiotics against these bacterial strains to avoid resistance and to prescribe appropriate treatment for the patients.